2023
DOI: 10.1155/2023/9610317
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on the Influence of Superplasticizer on Mechanical Behavior of Recycled Aggregate Concrete

Faruk Patowary,
Mohammad Al Amin Siddique

Abstract: Needs for renovation and efficient use of available land space have led to the destruction of numerous deteriorated civil structures. Consequently, a huge amount of concrete demolished waste is generated annually worldwide. This demolished concrete waste has created an extra burden on the environment and landfills, making the development projects unsustainable. Demolished waste can be recycled and reused for sustainable development and to reduce the demand for fresh natural aggregates (NA). However, the poor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Based on studies [6][7][8], several researchers have found that replacing 50% of the natural aggregates (NA) in RAC with RCA can reduce the RAC's compressive strength by up to 25%. Following a similar pattern to the drop in compressive strength, as reported in different studies, tensile strength splitting was seen to fall by as much as 39% with a total replacement of natural aggregates (NA) with RCA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies [6][7][8], several researchers have found that replacing 50% of the natural aggregates (NA) in RAC with RCA can reduce the RAC's compressive strength by up to 25%. Following a similar pattern to the drop in compressive strength, as reported in different studies, tensile strength splitting was seen to fall by as much as 39% with a total replacement of natural aggregates (NA) with RCA.…”
Section: Introductionmentioning
confidence: 99%
“…A small increase in mechanical strength and a reduction in the amount of water in the mixtures are the results of adding superplasticizers. PATOWARY and SIDDIQUE [8] claimed that a responsive superplasticizer may be used to control the rheology of newly manufactured cement-based products. The results of their study demonstrated that superplasticizers based on polycarboxylic ether (PCE) can be given other functions by adding certain chemical groups [12].…”
Section: Introductionmentioning
confidence: 99%